Non-cirrhotic Splenic-portal Thrombosis, non-tumoral Polycitemia Vera: an Infrequent Association - Samuel Sánchez Sánchez; Karina Rivero García; Osvaldo Rodríguez Morales; René Rivero Rodríguez (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
Polycitemia vera is included in the group chronic mieloproliferative neoplasias. It has an incidence below 2.5 every 100 000 people. The thrombotic forms represent only between 10.15 % of the cases. Splenic-portal thrombosis not associated to cirrhosis or neoplasias have an incidence below 5 every 10000 inhabitants, between 17-53 % are associated to any type of primary mieloproliferative syndrome. A case of a 70 year old patient who came to the doctor complainig of an abdominal pain of 15 day duration. Abdominal ultrasound showed a markedly ecogenic liver towards vascular structures, compatible with extensive thrombotic areas of the splenic-portal axis, corroborated later by contrast tomography. Bone morrow biopsy concluded a three series hyperplasia, the determination of JAK2V617F mutation was positive. The low incidence of polycitemia vera and its unusual way of presenting as thromobosis of splenic-portal system motivated the presentation of this case.